2015
DOI: 10.1002/etc.2847
|View full text |Cite
|
Sign up to set email alerts
|

Modeling food web structure and selenium biomagnification in lake macquarie, New South Wales, Australia, using stable carbon and nitrogen isotopes

Abstract: As a consequence of coal-fired power station operations, elevated selenium concentrations have been reported in the sediments and biota of Lake Macquarie (New South Wales, Australia). In the present study, an ecosystem-scale model has been applied to determine how selenium in a seagrass food web is processed from sediments and water through diet to predators, using stable isotopes (δ(13) C and δ(15) N) to establish the trophic position of organisms. Trophic position, habitat, and feeding zone were examined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…2013, Schneider et al. 2015, Azevedo‐Silva et al. 2016), to determine the effects of humans on ecosystem health (Mavraki et al.…”
Section: Introductionmentioning
confidence: 99%
“…2013, Schneider et al. 2015, Azevedo‐Silva et al. 2016), to determine the effects of humans on ecosystem health (Mavraki et al.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being an essential element excess concentration can cause adverse effects on biota (Jasonsmith et al, 2008;Savery et al, 2013). In the aquatic environment Se is introduced by plankton in particulate form, and therefore it is incorporated into organic matter and transferred from invertebrates to fish (Schneider et al, 2015). Globally, there is a growing interest in elucidating the results of Se and Hg interaction in aquatic ecosystems, as Se has been reported to exert a reducing effect against MeHg toxicity (Azad et al, 2019;Bjerregaard & Christensen, 2012;Burger et al, 2013b;Burger & Gochfeld, 2013a).…”
Section: Seleniummentioning
confidence: 99%
“…In relation to factors influencing biomagnification, trophic structure and diet have been reported to be key factors that help to understand trophodynamics, accumulation and biomagnification along food webs (Arcagni et al, 2013;Schneider et al, 2015). Studies have indicated that in networks composed of plankton, algae, invertebrates, macrophytes and fish, Se only biomagnifies in fish and its biomagnification potential could be related to the complexity of the food web (Arcagni et al, 2013;Jasonsmith et al, 2008;Mann et al, 2011;Økelsrud et al, 2016).…”
Section: Seleniummentioning
confidence: 99%
See 2 more Smart Citations